Can forest cities enhance both economic and ecological resilience? - Wang, Yameng; Zou, Fan; Wei, Feng; Hou, Mengyang; Jin, Huawang; Zhang, Mingyue (Frontiers in Ecology and Evolution, 2025)
How to balance the relationship between economy and ecology in order to cope with external shocks has become the key challenge for promoting sustainable regional development. Drawing on resilience theory, this paper applies a multi-period progressive difference-in-differences method to examine the impacts and mechanisms of the Forest City Selection system on economic resilience and ecological resilience using the panel data of Chinese cities from 2003 to 2022. The results show that the Forest City Selection encourages local governments to enhance economic resilience while maximizing the preservation of existing ecological space, thereby achieving synergy between urban economic resilience and ecological resilience through the optimized allocation of ecological and production spaces. Mechanism analyses indicate that technological progress in the production sector, upgrading of regional industrial structure, and ecological space utilization efficiency are the main channels through which the Forest City Selection fosters synergy between urban economic resilience and ecological resilience. The heterogeneity of this selection system is largely shaped by the combined effects between the transformation costs of shifting the economic resilience model and the opportunity costs of ecological construction. A coupled coordination model is further developed to demonstrate the synergistic effects of Forest City Selection in strengthening both economic and ecological resilience. Overall, this study provides empirical evidence that Forest City Selection promotes the joint improvement of economic and ecological resilience, offering a comprehensive perspective for advancing sustainable urban development.